1995
DOI: 10.2118/26468-pa
|View full text |Cite
|
Sign up to set email alerts
|

Deepwater Gulf of Mexico Turbidites— Compaction Effects on Porosity and Permeability

Abstract: The deepwater Gulf of Mexico is now a major area of activity for the U.S. oil industry. Compaction causes particular concern because most prospective deepwater reservoirs are highly geo-pressured and many have limited aquifer support; water injection may also be problematic. Thus, economic development may require significant drawdowns with ensuing compaction and its attendant problems.To address some of the issues associated with compaction, we initiated a special core-analysis program to study compaction effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 3 publications
(3 reference statements)
0
20
0
Order By: Relevance
“…Laboratory experiments have shown that such timedependent deformation is evident in a wide variety of sediments and sedimentary rocks (Cogan, 1976;Rongzun et al, 1987;Dudley et al, 1994;Ostermeier, 1995;among others). The mechanism of timedependent deformation in such materials has been attributed either to pore fluid expulsion under drained condition (Cogan, 1976;Karig, 1993;Hornby, 1998) or to pore pressure redistribution under undrained condition (Holzer et al, 1973;Jones and Wang, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Laboratory experiments have shown that such timedependent deformation is evident in a wide variety of sediments and sedimentary rocks (Cogan, 1976;Rongzun et al, 1987;Dudley et al, 1994;Ostermeier, 1995;among others). The mechanism of timedependent deformation in such materials has been attributed either to pore fluid expulsion under drained condition (Cogan, 1976;Karig, 1993;Hornby, 1998) or to pore pressure redistribution under undrained condition (Holzer et al, 1973;Jones and Wang, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…[2] Given that the deformation of most unconsolidated sands has been observed to depend on both state (contact area or porosity) and deformation rate, it is necessary to include these effects when constructing an appropriate constitutive law [Yale et al, 1993;Ostermeier, 1995;Chang et al, 1997;Hagin and Zoback, 2004]. A natural choice for such a law is the rateand-state variable friction law, since it already contains the necessary terms and was empirically derived from laboratory observations in a concise mathematical form [e.g., Dieterich, 1978Dieterich, , 1979 and has a physical basis in thermally activated creep at high-stress asperity contacts [Nakatani, 2001;Rice et al, 2001;Beeler, 2004;Nakatani and Scholz, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…For compaction of quartz sand in friction experiments [e.g., Richardson and Marone, 1999], strain rate decays according to a power law function of porosity during a hold. In volumetric creep tests on unconsolidated sands from the upper terminal zone of the Wilmington field (and others from the Gulf of Mexico), strain rate decays according to a power law of time, under conditions of hydrostatic stress [Ostermeier, 1995;Chang et al, 1997;Hagin and Zoback, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Ostermeier (1995) observed creep strain under constant hydrostatic loading conditions in saturated Gulf of Mexico turbidite sands and characterized his observations using a standard linear solid viscoelastic model. Dudley et al (1994) observed similar behavior in saturated Gulf of Mexico turbidite sands under uniaxial strain conditions and modeled the creep strain using a power law function of time.…”
Section: Introductionmentioning
confidence: 99%